The Social teaching of archbishop John Williams - Knox, R. Buick - (Studies in church history, 1972)
In English history the seventeenth-century upheavals were of great importance in leading to parliamentary government, religious toleration and autonomous science. In both popular belief and scholarly teaching the Puritans have been given much credit for these developments. However, the process was much more tentative and complex than has often been supposed. For example, Milton is remembered as a prophet of popular liberty but his experience in the practical affairs of government drove him to aim at government by a virtuous aristocracy which was most likely to arise from among those who had property and the consequent time to spare for political activity. The recent awakening of interest in the more extreme sectarian and revolutionary movements on the Continent and in England has brought into sharper focus the relative conservatism of many of the Puritans and has given the English Civil War and its aftermath the appearance of a rift within the landowning and propertied classes. Science owed much to the current questioning of tradition and of authority but it also owed not a little to the diligence of several royalist clergy and laity who in their years of unemployment during the interregnum devoted themselves to scientific observations and experiments; the genius of Sir Christopher Wren was maturing during these years. Families and individuals were often torn by conflicts of loyalties. There was the loyalty to the possibility of a better and more balanced society free from ecclesiastical impositions and from the exercise of power without responsibility; there was also the loyalty to the existing structure of society which, for all its faults, was a fence protecting the country from mob rule and communal chaos. Many changed from side to side in the years before, during and after the Civil War and they did so not simply out of a prudential desire to be on the winning side but because they were apprehensive of the revolutionary trends in the movement in which they had got involved.